The Role Of Forestry Extension Agents In Community Empowerment Farmers Group Pasar Village, Forest Management Unit Iv Balige District Toba Regency - Sarintan Efratani Damanik; Tri Astuti; Rozalina; Aqsal Wibiandra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Empowerment is an effort to build community power by encouraging, motivating and awakening awareness of the potential possessed and trying to develop it. Means encouraging them to become more involved in decisions and activations that fulfill their work. Formulation of the problem in this study how the role of forestry extension agents in community empowerment and farmer group attitudes in the extension program in the Village Market Area Forest Management Unit IV Balige District Toba. The purpose of this study was to determine the role of extension workers in community empowerment and the attitude of farmer groups in forestry extension programs in Pasar Village, Forest Management Unit IV, Balige District, Toba Regency. The role of forestry extension and farmer group attitude to extension workers in community empowerment programs tend to be said to be moderate, because of some of the programs provided by extension workers are not in accordance with the wishes and needs of farmer groups, it is also influenced by extension activities are usually carried out outside the Village Market, and not all people can follow the extension activities and training provided by the forestry extension.